Risk Factors for Surgical Shunting in a Large Cohort with Ischemic Priapism. Issue 12 (15th November 2020) - Zhao, Hanson; Dallas, Kai; Masterson, John; Lo, Eric; Houman, Justin; Berdahl, Carl; Pevnick, Joshua; Anger, Jennifer T.
Abstract: Background: Ischemic priapism is treated with a stepwise algorithm, but some patients may benefit from immediate shunt placement. Aim: To identify risk factors for surgical shunt placement in a large series of patients with ischemic priapism. Methods: We identified all patients presenting to our institution with ischemic priapism from January 2010 to December 2018. Multivariable was performed to assess risk factors for surgical shunting. Receiver operating characteristic curve analysis (Youden Index) was used to assess which cutoff time for the duration of priapism was most predictive requiring shunting. Outcomes: We assess risk factors for surgical shunting and what duration of priapism was most predictive of requiring a shunt. Results: We identified a total of 169 ischemic priapism encounters from 143 unique patients, of which 26 (15%) encounters resulted in a surgical shunt. Patients treated with a shunt had longer priapism durations than those without (median 36 vs 10 hours, P < .001). Independent predictors of a surgical shunt on multivariate logistic regression were the duration of priapism in hours (odds ratio: 1.05, 95% confidence interval: 1.02–1.10; P < .001) and history of prior priapism (odds ratio: 3.15, 95% confidence interval: 1.03–9.60; P = .045). Receiver operating characteristic curve analysis using priapism duration to predict the need for shunt generated an area under curve of 0.83. A duration of 24 hours correlated to a sensitivity of 0.77 and specificity of 0.90. Clinical Implications: These results can be used to counsel future patients and assist in the decision-making process for providers. Strengths & Limitations: This is one of the largest series of priapism in the literature. Most (74%) of the priapism were due to intracavernosal injections so the results may not be generalizable to populations with different priapism etiologies. Conclusion: In this study of 169 priapism encounters, we found that the priapism duration and history of prior priapism were independent predictors of surgical shunt placement. These results can aid urologists in the counseling and decision-making process of these challenging cases.